Hunting activity in the Cerrado of Maranhão: techniques and associated sociocultural factors - Cardoso dos Santos, Pedro Victor; Silva Ferreira, Felipe; Vieira Brito, Samuel (Ethnobiology and Conservation, 2024)
Hunting activity and the use of fauna are ancient practices that reveal meaningful connections with biodiversity. Such activities present patterns of use and consumption linked to sociocultural factors, such as land situation and financial condition. However, hunting pressure can cause the decline of wild animal populations, which is a conservationist concern. For this reason, this research aims to provide an inventory of the most cited species during hunting and analyze the sociocultural characteristics of those practicing this activity in a Cerrado location in Northeast Brazil. The information was obtained through semi-structured questionnaires, complemented by informal conversations, with 21 hunters aged between 18 and 72 years. Additionally, the Generalized Linear Model (GLM) verified whether socioeconomic factors influence hunting activity in the municipality of Anapurus - MA. The analyses reported 23 taxa were cited, of which 20 identified at species level and 3 at genus level, with their uses linked to food, and among the two groups cited: mammals and birds, the second group had the highest number of citations. The analyzed data showed that none of the socioeconomic factors selected could affect hunting in the municipality, implying that cultural and traditional aspects are the primary influence.